Theaters of Citizenship Aesthetics and Politics of Avant-Gardist Performance in Egypt - Pahwa, Sonali (Northwestern University Press, 2020)
Theaters of Citizenship investigates the Egyptian movement for free theater, arguing that it evolved from an avant-gardist movement to an undercommons of revolutionary cultural practice. Using historiography, ethnography, and performance analysis, the book tells a story of this avant-garde from 2004-2014, analyzing its staging of rights claims, generational identity politics, and post-revolution citizenship. Using Moten and Harney's theory of the undercommons, a space-time for politicized cultural practice, the book extends avant-gardist theater theory to consider the revolutionary potential of performance within and outside theater spaces. Pahwa considers the performer's bodily repertoire as a medium of cultural and political citizenship, drawing on Diana Taylor's concept of repertoire, and expanding it to account for how performance mediates futurist culture and revolutionary practice.